Body Mass Index, Perceived Weight, and Self-Rated Health among South Korean Adults: Conjoint Effect on Health? - Soyoung Kwon (AIMS Press, 2017)
The prevalence of overweight and obesity is rising rapidly in many countries, including South Korea. The present study examined the association between weight perception and self-rated health, independent of body weight status, as well as how weight status and perceived weight status intersect and relate to the self-rated health among adults in South Korea. Data were from 722 men and 800 women in 2010 Korean General Social Survey. Results showed that over half of Korean adults perceived their weight incorrectly with a fair agreement (men ƙ = 0.36; women ƙ = 0.31). Multivariate analyses indicated that poor/fair self-rated health had no significant association with body weight status, measured by self-reported weight and height, but it had a significant association with perceived weight status in men. The intersectionality analysis in which weight status and weight perceptions were cross-classified indicated that both measured and perceived weight status should be taken into account for the indicator of self-rated health as well as for better understanding of weight-related health consequences.